Diretrizes de apoio ao processo de construção de sistemas conversacionais de recomendação acessíveis: um estudo com usuários idosos - Araujo, Lucas; Rodrigues, Kamila; Manzato, Marcelo (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
Elderly individuals often face challenges when using computational tools due to physical, cognitive, and hearing limitations. To improve accessibility, adaptive conversational systems have emerged as a promising option. This work provided guidelines for developing accessible conversational recommendation systems. Using the PLuRaL method, it was possible to conduct tests and evaluations in a participatory manner. In addition to the guidelines, the work presents various discussions that pave the way for new research and explore future possibilities in the development of more inclusive conversational technologies.